Experimental study of the dynamic stall noise on an oscillating airfoil. (27th October 2022) - Raus, David; Cotté, Benjamin; Monchaux, Romain; Jondeau, Emmanuel; Souchotte, Pascal; Roger, Michel
Abstract: In this paper, the noise emitted by an oscillating NACA0012 airfoil at Reynolds number R e c = 2 . 1 × 1 0 5 is studied. Combined far-field noise and surface pressure measurements are performed in order to investigate the effect of the amplitude of motion α 1 and reduced frequency k on the emitted far-field noise. These two parameters can be combined using the reduced pitch rate k ⋆ = α 1 k that is shown to be the most relevant parameter in this study. The dynamic stall noise is characterized by an increase of the noise amplitude at frequencies below 700 Hz and takes place each time the airfoil incidence increases over the critical dynamic stall angle. For a low reduced pitch rate ( k ⋆ = 1 . 2 × 1 0 − 3 ), a quasi-steady regime is obtained, with the light-stall and deep-stall regimes commonly observed for a static airfoil taking place during the pitching motion. For a higher pitch rate ( k ⋆ = 13 . 1 × 1 0 − 3 ), an increase of the duration and amplitude of the broadband noise occurring at the stall onset is identified. For all the reduced pitch rates investigated, a delay in the apparition of the stall noise is observed in comparison with the static stall noise, leading to a hysteresis of the stall noise as a function of the angle of attack. Highlights: Surface pressure and acoustic measurements are performed on a pitching airfoil. Quasi-steady and dynamic stall regimes are considered. The light and deep stall noise regimes are observed for a quasi-steady oscillation. The amplitude and length of the stall onset noise increase with the reduced pitch rate. A hysteresis of the stall noise as a function of the angle of attack is observed.